A small-distributed aerodynamic brake prototype and its effects on the vertical dynamics of high-speed electromagnetic suspension maglevs. (October 2022) - Weng, Jingjing; Tian, Chun; Ma, Tianhe; Wu, Mengling
Aerodynamic braking is a clean and environmentally friendly braking mode, and it does not use mechanical friction as its braking force. In this study, we discuss the development of a small-distributed aerodynamic brake prototype and its structure, working principle, ground test and test results. A computational fluid dynamics (CFD) method is developed to record the aerodynamic forces of the prototype, and the simulation results are validated with the wind tunnel test. On the basis of the CFD simulation, the panel opening and braking processes are modelled to analyse the vertical dynamic characteristics of a high-speed electromagnetic suspension maglev with aerodynamic brakes. In addition, a vehicle, guideway and levitation controller are modelled. Finally, a three-car system dynamic model is used to study the effects of the opening time, initial braking position and feedback gains. The aerodynamic forces of the first car show the most significant changes when the braking panels are opened. The increase in the longitudinal force is 15 461.16 N, and the vertical force varies from a lift force of 35 342.98 N to a downforce of 40 721.35 N. The maximum guideway deflection decreases as the opening time increases. The difference between the deflections recorded at the opening time of 0.064 s and 0.6 s is 1.2 mm. Furthermore, the vertical acceleration decreases as the opening time increases. The condition under which the vehicle brakes when the first car enters the object guideway has the maximum effect on the deflection of the guideway. To ensure levitation stability, influenced by the vertical change of the first car, a high feedback gain for the levitation clearance change is required. However, the levitation stability with aerodynamic brakes has low sensitivity to the feedback gains for the observed velocity and acceleration of the system.